Detection Of Salmonella Spp. And Salmonella Enteritidis In Turkey Samples By PCR Method - RAMYA PUTTURU,; KRISHNAIAH NELAPATI,; TIRUPATIREDDY EVURI,; BINDUKIRANMAYI CH, (International Journal of Pharma and Bio Sciences, 2012)
A total of 60 samples (20 each of turkey meat, faeces and cloacal swab samples) collected from different sources were subjected to cultural and PCR methods for the presence of Salmonella and Salmonella enteritidis. Primers for invA and sefA gene were used for Salmonella and S.enteritidis respectively. Out of 60 samples, 49 were positive for Salmonella spp. i.e. turkey meat-14(70%), turkey cloacal swabs-17(85%), turkey faeces-18(90%) by PCR methods, whereas 43 were positive by cultural method i.e. turkey meat-12(60%), turkey cloacal swabs-15(75%), turkey faeces-16(80%). Out of 49 positive for Salmonella by PCR method, 36 (turkey meat-11, turkey cloacal swabs-13, turkey faeces-12) were positive for S.enteritidis. Selective enrichment with Rappaport-Vassilidias (RV) broth and Tetrathionate (TT) broth were superior over Selenite-F (SF) and Selenite cysteine (SC) broths.